Diamagnetic rotation glass, magneto-optical fiber, magneto-optical element and optical instrument

By adjusting the ratio of oxides such as Bi2O3, Pb3(BO3)2, an inverse magneto-optical glass with high Wilder constant and temperature independent characteristics was prepared, which solved the problems of small Wilder constant and temperature sensitivity in the prior art, and improved the The stability of the laser system.

CN119409414APending Publication Date: 2025-02-11XIAN INST OF OPTICS & PRECISION MECHANICS CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411401691.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing inverse magneto-optical glass has a small Wild constant and is temperature sensitive, making it difficult to meet the performance requirements of magneto-optical isolators in high-energy laser systems.

Method used

In terms of molar percentage, including 50 to 80 mol% of Bi2O3, 5 to 35 mol% of glass Pb3(BO3)2, 3 to 10 mol% of BaO, 1 to 8 mol% of Ga2O3, 0 to 3 mol% of Cs2O and 0.1 to 0. The 3mol% Al2O3 reverse magneto-optical glass formula improves the Wilder constant and reduces temperature dependence by adjusting the structure and composition of the glass network.

Benefits of technology

The high Wilder constant (>0.05min/Oe.cm@1064nm) and temperature independent characteristics of inverse magneto-rotating glass are realized, which simplifies device design and improves the stability and reliability of the laser system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409414A_ABST
    Figure CN119409414A_ABST
Patent Text Reader

Abstract

The invention provides a diamagnetic optical rotation glass, a magneto-optical fiber, a magneto-optical element and an optical instrument.The diamagnetic optical rotation glass is prepared from, by mole percent, 50%-80% of Bi2O3, 5%-35% of glassy state Pb3 (BO3) 2, 3%-10% of BaO, 1%-8% of Ga2O3, 0%-3% of Cs2O and 0.1%-3% of Al2O3, and the total mole percent of all the components is 100%. The glassy-state Pb3 (BO3) 2 is added into the formula components to improve corrosion to a crucible in the glass melting process and inhibit volatilization of low-melting-point boric acid, and the prepared bismuthate-doped glass has the characteristics of ultralow mid-infrared loss, high Vildet constant of an infrared band and extremely low Vildet constant temperature coefficient, and can be used for preparing a high-temperature-resistant glass material. The optical property of the inverse magnetic rotation glass is controllable, the optical uniformity is improved, and the performance requirement of low insertion loss of an optical isolator in an infrared high-power laser system can be met. The Vierdean constant of the inverse magnetic rotation glass provided by the invention shows a remarkable temperature-independent characteristic, and the inverse magnetic rotation glass can be used for preparing magneto-optical fibers, magneto-optical elements and optical instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical glass manufacturing, and in particular relates to a reverse magnetic rotation glass, a magneto-optical optical fiber, a magneto-optical element and an optical instrument. Background Art

[0002] Mid-infrared high-power all-solid-state lasers and fiber lasers are widely used in fusion energy, laser weapons, laser processing, and defense industry. However, during the use of lasers, high-energy reflected light can damage the front-end system (such as the resonant cavity and seed source), which in turn poses a serious threat to the reliability of the laser system. Faraday optical isolation devices can ensure unidirectional transmission of the laser system and isolate reverse light by adding an additional magnetic field in the propagation direction of light to deflect the polarization plane of linearly polarized light by a certain angle. They are necessary devices in high-power laser systems to prevent optical feedback in the optical system from damaging the laser and other magneto-optical components. Magneto-optical materials, as the core dielectric materials of magneto-optical isolation devices, should have the characteristics of high Verdet constant, low Verdet constant temperature coefficient, high laser damage threshold, low light absorption coefficient, and high optical uniformity to meet the performance requirements of optical isolators and achieve miniaturization.

[0003] At present, the magneto-optical isolators commonly used in laser systems generally use terbium-containing terbium gallium garnet (TGG) crystals and terbium-doped boron aluminum silicon magneto-optical glass as paramagnetic medium materials. These paramagnetic medium materials have a large Verdet constant, but their Verdet constant shows a large dependence on temperature (the Verdet constant temperature coefficient is about 0.3 / ℃). Rapid temperature changes will cause the magneto-optical coefficient and deflection angle of the paramagnetic medium to drift significantly, causing the optical isolation effect of the magneto-optical isolator to deteriorate or fail, which seriously limits the application of paramagnetic materials in high-energy laser systems. Diamagnetic glass generally contains heavy metal ions with high polarizability and no permanent electron orbital magnetic moment. Its Verdet constant is almost unaffected by temperature. Therefore, devices made of diamagnetic glass do not require temperature compensation mechanisms and have the characteristics of simple structure and small size. However, existing diamagnetic glass has the following problems: the Verdet constant is small. The Verdet constant of the currently commercially available PbO-SiO2 system series flint glass (SF6, SF57, SF59) is at the level of 0.02~0.03min / Oe.cm@1064nm; it is difficult to prepare. When the heavy metal oxide content in the glass is high, the crucible erosion will be accelerated during the melting process. In addition, the density and melting point of the components vary greatly, which makes it difficult to control the glass performance.

[0004] Therefore, how to find a suitable formula for reverse magnetic optical rotation glass so that it has a high Verdet constant and is insensitive to temperature is a technical challenge faced by technicians in this field. Summary of the invention

[0005] In view of the defects and shortcomings of the prior art, the object of the present invention is to provide a reverse magnetic rotation glass, a magneto-optical optical fiber, a magneto-optical element and an optical instrument.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0007] A reverse magnetic optical rotation glass comprises the following components, measured in molar percentage: 50-80 mol% of Bi2O3, 5-35 mol% of glassy Pb3(BO3)2, 3-10 mol% of BaO, 1-8 mol% of Ga2O3, 0-3 mol% of Cs2O and 0.1-3 mol% of Al2O3, wherein the total molar percentage of each component is 100%.

[0008] The present invention also has the following technical features:

[0009] Specifically, in terms of molar percentage, it includes the following components: 76 mol% of Bi2O3, 15 mol% of glassy Pb3(BO3)2, 5 mol% of BaO, 3 mol% of Ga2O3, 0.5 mol% of Cs2O and 0.5 mol% of Al2O3.

[0010] Furthermore, the 1064nm absorption coefficient of the reverse magnetic rotation glass is 0.002-0.006cm -1 , 1064nm Verdet constant is 0.050~0.064min / Oe.cm, refractive index is 2.30~1.68, and glass transition temperature is 310~350℃.

[0011] Furthermore, the glassy Pb3(BO3)2 is prepared by the following steps:

[0012] Step 1, grinding and mixing the formulated amount of PbO and B2O3, and drying to obtain a mixed material A;

[0013] Step 2, under stirring conditions, heating the mixed material A to 750-850° C. to melt, to obtain a mixed solution B;

[0014] Step 3, pouring the mixed solution B into a copper mold at room temperature, and grinding it after cooling to obtain;

[0015] Wherein, the molar ratio of PbO to B2O3 in step 1 is (1.3-1.6):1.

[0016] Furthermore, the preparation of the reverse magnetic rotation glass is carried out in a pure oxygen atmosphere glove box, comprising the following steps:

[0017] Step 1, mixing and grinding Bi2O3, glassy Pb3(BO3)2, BaO, Ga2O3, Cs2O and Al2O3 according to the formula amount to obtain a batch material;

[0018] Step 2, melting, clarifying and homogenizing the batch materials to obtain reverse magnetically rotating glass liquid;

[0019] Step 3, quenching, forming, heat preservation and cooling the reverse magnetic optical rotation glass liquid to obtain the product.

[0020] Furthermore, in step 2, the preparation melting temperature is 950-1000°C, and during the melting process, ultra-dry oxygen is continuously blown into the furnace at a rate of 0.5L / min; the clarification temperature is 960-1100°C, and the clarification time is 10-20min; the homogenization speed is 15-30r / min, and the temperature after homogenization is 750-850°C.

[0021] Furthermore, in step 3, the quenching forming temperature is 230-250°C, the holding temperature is 290-400°C, the holding time is 240-720 min, and the cooling rate of the cooling treatment is -2--10°C / h.

[0022] The present invention also protects a magneto-optical optical fiber, wherein the glass preform is made of the reverse magnetic rotation glass.

[0023] The present invention also protects a magneto-optical element, which is made of the reverse magnetic rotation glass.

[0024] The present invention also protects an optical instrument, which is made of the reverse magnetic rotation glass.

[0025] Compared with the prior art, the present invention has the following technical advantages:

[0026] (1) The reverse magnetic optical rotation glass provided by the present invention has high mechanical properties and thermal stability. The Verdet constant in the near-infrared band can reach >0.05min / Oe.cm@1064nm (23°C), which is more than twice that of the existing commercial reverse magnetic optical rotation glass (SF6, SF57, SF59). Its Verdet constant shows a significant temperature-independent characteristic. The device prepared by using it does not require a temperature compensation system, making the device structure compact and more stable.

[0027] (2) The reverse magnetic rotation glass provided by the present invention has good stability, can be drawn into magneto-optical optical fiber, has a wide infrared transmission range and a high laser damage threshold, and can be widely used in magneto-optical devices in the 0.4-4 μm band.

[0028] The specific contents of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a visible light-near infrared-mid-infrared transmission spectrum of 2 mm thick glass prepared in Example 1 of the present invention.

[0030] Figure 2 The deflection angle of 1064nm linear polarized light in a cavity with a magnetic field strength of 0.97T for 5mm thick glass prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by any ordinary technician in the field belong to the scope of protection of the present invention.

[0032] It should be noted that all raw materials in the present invention, unless otherwise specified, are raw materials known in the art.

[0033] The technical terms involved in the present invention are explained below:

[0034] Reverse magnetic optical glass refers to: a transparent magneto-optical functional glass that only produces an induced magnetic moment opposite to the direction of the magnetic field under the action of an external magnetic field. When polarized light passes through the magneto-optical glass, the polarization plane is positively deflected, thereby showing reverse magnetism, and its Verdet constant is greater than 0.

[0035] Glassy Pb3(BO3)2 refers to: Lead borate is a white crystalline solid with Pb 2+ and BO3 3- Arranged according to certain rules, a periodic lattice structure is formed. Glassy Pb3(BO3)2 is an amorphous oxide material made by high-temperature melting and rapid cooling. Its atomic structure is long-range disordered, and the melting temperature can be increased through three-dimensional structural cross-linking.

[0036] The technical concept of the present invention is: based on the positive correlation between the dispersion rate of the material and the Verdet constant, and the dispersion is related to the microscopic parameters such as the electronic structure, energy level distribution, interaction and collective vibration mode of atoms or molecules; the dispersion of the glass material is related to the theoretical dispersion of each composition. Taking the theoretical dispersion of each oxide as the starting point, the network former Bi2O3 with high refractive index and high dispersion is selected to construct the glass network, and the glass network is hybridized by introducing glass network intermediates and network exosomes such as B2O3, PbO, BaO, Ga2O3, Cs2O, Al2O3, etc., to suppress the glass crystallization trend caused by the high content of heavy metal oxides while adjusting the refractive index and dispersion of the glass. At the same time, by adjusting the Bi / Pb and Bi / B ratios to adjust the content and molar refractive index of non-bridging oxygen in the glass network, the Verdet constant of the glass can be improved. The introduction of PbO and B2O3 through glassy Pb3(BO3)2 can avoid the corrosion of the crucible during the glass melting process, suppress the large amount of volatilization of low-melting-point boric acid, and achieve effective control of the optical properties of the glass.

[0037] Specifically, BaO is an intermediate oxide, used as a flux, which can increase transparency, reduce the thermal expansion coefficient, and adjust the chemical stability and refractive index of the glass. Al2O3 is an intermediate oxide, and adding a small amount of Al2O3 can reduce the crystallization tendency of the glass and reduce the expansion coefficient of the glass, thereby improving the thermal stability of the glass, and improving the chemical stability and mechanical strength of the glass.

[0038] The present invention discloses a reverse magnetic optical rotation glass, which comprises the following components, measured in molar percentage: 50-80 mol% of Bi2O3, 5-35 mol% of glassy Pb3(BO3)2, 3-10 mol% of BaO, 1-8 mol% of Ga2O3, 0-3 mol% of Cs2O and 0.1-3 mol% of Al2O3, and the molar percentages of the components add up to 100%.

[0039] Preferably, the following components are included, in molar percentage: 76 mol% Bi2O3, 15 mol% glassy Pb3(BO3)2, 5 mol% BaO, 3 mol% Ga2O3, 0.5 mol% Cs2O and 0.5 mol% Al2O3.

[0040] Preferably, the 1064nm absorption coefficient of the reverse magnetic rotation glass is 0.002-0.006cm -1 , 1064nm Verdet constant is 0.050~0.064min / Oe.cm, refractive index is 2.30~1.68, and glass transition temperature is 310~350℃.

[0041] Preferably, the preparation of the reverse magnetic rotation glass is carried out in a pure oxygen atmosphere glove box, comprising the following steps:

[0042] Step 1, mixing and grinding Bi2O3, glassy Pb3(BO3)2, BaO, Ga2O3, Cs2O and Al2O3 according to the formula amount to obtain a batch material;

[0043] Step 2: Melting, clarifying and homogenizing the batch materials to obtain reverse magnetically rotating glass liquid; wherein the melting temperature is 950-1000°C, the clarifying temperature is 960-1100°C, the clarifying time is 10-20min, the homogenizing speed is 15-30r / min, and the temperature after homogenization is 750-850°C.

[0044] Step 3, quenching, forming, heat preservation and cooling the reverse magnetic optical rotation glass liquid to obtain the obtained product. The quenching forming temperature is 230-250°C, the heat preservation temperature is 290-400°C, the heat preservation time is 240-720min, and the cooling rate of the cooling treatment is -2--10°C / h.

[0045] Wherein, the glassy Pb3(BO3)2 is prepared by the following steps:

[0046] Step 1, grinding and mixing the formulated amount of PbO and B2O3, and drying to obtain a mixed material A;

[0047] Step 2, under stirring conditions, heating the mixed material A to 750-850° C. to melt, to obtain a mixed solution B;

[0048] Step 3, pouring the mixed solution B into a copper mold at room temperature, and grinding it after cooling to obtain;

[0049] Wherein, the molar ratio of PbO to B2O3 in step 1 is (1.3-1.6):1.

[0050] In the present invention, in order to inhibit the devitrification of the glass caused by the reduction of heavy metal ions, the formula weighing and mixing are carried out in a pure oxygen atmosphere glove box with ultra-low water content (water content <1ppm), and during the melting process, ultra-dry oxygen is continuously blown into the furnace chamber at a rate of 0.5L / min to ensure that the glass has a low mid-infrared hydroxyl absorption coefficient.

[0051] The reverse magnetic rotation glass provided by the present invention is tested for relevant performance parameters according to the following method:

[0052] The color of the glass state and after annealing is determined by visual inspection, the absorption coefficient of 1064nm is tested by the colorless glass absorption coefficient test standard GB / T 7962.9, and the Verdet constant is tested by the Faraday magneto-optical effect and Malus formula. The specific method is: the Verdet constant test platform composed of laser, polarizer, analyzer, magnetic field and light detector is used. Without placing the test sample, the analyzer is rotated 360°, and the rotation angle and the detected light intensity are recorded. The angle α between the analyzer and the transmission axis of the polarizer when the detected light intensity reaches the maximum value and the Faraday magneto-optical rotation angle θ are recorded as α b and θ b Keeping the initial light intensity, magnetic field strength and other conditions unchanged, place the sample to be tested in the magnetic field, rotate the analyzer 360°, record the rotation angle and the detected light intensity, and the α and θ corresponding to the maximum detected light intensity are recorded as α and θ respectively. m and θ m By subtracting the analyzer rotation angle corresponding to the maximum detection light intensity when there is a sample to be tested and when there is no sample to be tested in the test system, the Faraday magneto-optical rotation angle θ of the sample to be tested can be obtained. Combining the magnetic field intensity B set during the test and the length L of the sample to be tested, the Verdet constant of the sample to be tested can be calculated according to the following formula:

[0053]

[0054] Example 1

[0055] In accordance with the above technical solution, this embodiment provides a reverse magnetic optical rotation glass, which is prepared according to the following method:

[0056] Step 1, mixing and grinding Bi2O3, glassy Pb3(BO3)2, BaO, Ga2O3, Cs2O and Al2O3 according to the formula shown in Table 1 to obtain a batch material;

[0057] Wherein, glassy Pb3(BO3)2 is prepared according to the following method:

[0058] (1) PbO and B2O3 are weighed in a molar ratio of 3:2, ground and mixed thoroughly, and then dried to obtain a mixed material A;

[0059] (2) placing the mixed material A into a transparent quartz crucible and heating and melting it at 820-850° C., stirring it with a quartz paddle at a speed of 30 r / min, to obtain a mixed liquid B with a uniform composition;

[0060] (3) rapidly pouring the mixed solution B into a room temperature copper mold, and grinding it after cooling to obtain a glassy Pb3(BO3)2 powder;

[0061] Step 2, directly adding the batch material into a preheated platinum crucible without atmosphere protection, with a melting temperature of 1000°C, stirring with a platinum paddle, clarifying at 1000°C for 20 minutes, homogenizing at a speed of 20r / min, and then cooling to 750-800°C to obtain a reverse magnetically active glass material liquid;

[0062] Step 3: pour the reverse magnetic optical rotation glass liquid into the preheated copper mold, keep it in an annealing furnace at 400° C. for 8 hours, and then cool it naturally to room temperature to obtain the reverse magnetic optical rotation glass.

[0063] The glass obtained in this embodiment was processed into a glass sheet with a diameter of 10×2 mm and the two end surfaces were precisely polished, and a visible-infrared transmission spectrum test was performed. Figure 1 The glass sheet was placed on an existing magneto-optical effect test platform to test its Verdet constant at an incident light wavelength of 1064 nm. The results are shown in Table 1. The visible light-near infrared-mid-infrared transmission spectrum of the glass sheet with a size of 10×2 mm processed from the glass prepared in this embodiment is shown in Table 1. Figure 1 As shown, it has good transmittance in a wide range of 0.5 to 4.5 μm.

[0064] The glass prepared in this embodiment is processed into a 5 mm thick glass sheet. The deflection angle of the 1064 nm linear polarization light in a 0.97 T magnetic field is as follows: Figure 2 As shown, the Verdet constant can be directly calculated by the deflection angle, magnetic field strength and material thickness, and further calculated to be 0.064min / Oe.cm@1064nm (23°C).

[0065] Example 2

[0066] The preparation method of the reverse magnetic optical rotation glass disclosed in this embodiment has the same steps as the preparation method disclosed in Example 1, and the only difference is the ratio of the components. The ratio of the components used in this embodiment is shown in Table 1.

[0067] The glass obtained in this embodiment was processed into a glass sheet of 10×2 mm in diameter and the two end faces were precisely polished. Then, a visible-infrared transmission spectrum test was performed. The measured absorption coefficient at 1064 nm was as follows: Figure 1 As shown; the aforementioned glass sheet was placed on an existing magneto-optical effect test platform to test its Verdet constant at an incident light wavelength of 1064nm, and the results are shown in Table 1.

[0068] Example 3

[0069] The preparation method of the reverse magnetic optical rotation glass disclosed in this embodiment has the same steps as the preparation method disclosed in Example 1, and the only difference is the ratio of the components. The ratio of the components used in this embodiment is shown in Table 1.

[0070] The glass obtained in this embodiment was processed into a glass sheet of 10×2 mm in diameter and the two end faces were precisely polished. Then, a visible-infrared transmission spectrum test was performed. The measured absorption coefficient at 1064 nm was as follows: Figure 1 As shown; the aforementioned glass sheet was placed on an existing magneto-optical effect test platform to test its Verdet constant at an incident light wavelength of 1064nm, and the results are shown in Table 1.

[0071] Example 4

[0072] The preparation method of the reverse magnetic optical rotation glass disclosed in this embodiment has the same steps as the preparation method disclosed in Example 1, and the only difference is the ratio of the components. The ratio of the components used in this embodiment is shown in Table 1.

[0073] The glass obtained in this embodiment was processed into a glass sheet of 10×2 mm in diameter and the two end faces were precisely polished. Then, a visible-infrared transmission spectrum test was performed. The measured absorption coefficient at 1064 nm was as follows: Figure 1 As shown; the aforementioned glass sheet was placed on an existing magneto-optical effect test platform to test its Verdet constant at an incident light wavelength of 1064nm, and the results are shown in Table 1.

[0074] Example 5

[0075] The preparation method of the reverse magnetic optical rotation glass disclosed in this embodiment has the same steps as the preparation method disclosed in Example 1, and the only difference is the ratio of the components. The ratio of the components used in this embodiment is shown in Table 1.

[0076] The glass obtained in this embodiment was processed into a glass sheet of 10×2 mm in diameter and the two end faces were precisely polished. Then, a visible-infrared transmission spectrum test was performed. The measured absorption coefficient at 1064 nm was as follows: Figure 1 As shown; the aforementioned glass sheet was placed on an existing magneto-optical effect test platform to test its Verdet constant at an incident light wavelength of 1064nm, and the results are shown in Table 1.

[0077] Glass composition (mol%) Example 1 Example 2 Example 3 Example 4 Example 5 <![CDATA[Bi2O3]]> 76 71 66 61 56 <![CDATA[Pb3(BO3)2]]> 15 20 25 30 35 BaO 5 7 5 3 6 <![CDATA[Ga2O3]]> 3 1 3 5 2 <![CDATA[Cs2O]]> 0.5 0.3 0.1 0 0.7 <![CDATA[Al2O3]]> 0.5 0.7 0.9 1 0.3 Glass transition temperature () 323.6 335.2 332.1 329.8 326.1 Glassy state good good good good good Color after annealing Light yellow Light yellow Light yellow Light yellow Light yellow <![CDATA[1064nm absorption coefficient (cm -1 )]]> 0.002 0.003 0.003 0.006 0.005 1064nm Verdet constant (min / Oe.cm) 0.064 0.057 0.054 0.055 0.051

[0078] Table 1. Composition ratios and test results of Examples 1 to 5

[0079] From the measurement results in Table 1, we can see that:

[0080] The diamagnetic optically active glass obtained in Examples 1 to 5 is transparent and has no crystallization, and has no obvious absorption peak in the mid-infrared band, indicating that the hydroxyl content in the prepared diamagnetic optically active glass is extremely low, and the flat infrared transmittance range allows it to be applied to farther wavelengths; at an incident light wavelength of 1064nm, the Verdet constant of the diamagnetic magneto-optical glass provided by the present invention can reach up to 0.064min / Oe.cm, which is much higher than the existing commercial SF-59 and SF-57 diamagnetic magneto-optical glass materials.

[0081] The reverse magnetic optical rotation glass provided by the present invention has good stability, can be drawn into magneto-optical optical fiber, has a wide infrared transmission range and a high laser damage resistance threshold, and can also be used to manufacture magneto-optical components including magneto-optical isolators, wherein the prepared magneto-optical isolators can be applied to 0.4-4 μm laser systems. The magneto-optical component made of the reverse magnetic optical rotation glass provided by the present invention after optical design can ensure the unidirectional transmission of incident light in the laser system and isolate the reverse light, thereby preventing the optical feedback in the optical system from damaging the laser and other optical components, maintaining the stability of the laser light source system, and effectively eliminating the noise of the laser source and suppressing the frequency drift.

[0082] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0083] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0084] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A reverse magnetic optical rotation glass, characterized in that: In terms of molar percentage, it includes the following components: 50-80 mol% Bi2O3, 5-35 mol% glassy Pb3(BO3)2, 3-10 mol% BaO, 1-8 mol% of Ga2O3, 0-3 mol% of Cs2O and 0.1-3 mol% of Al2O3, the molar percentages of each component totaling 100%.

2. The reverse magnetic optical rotation glass according to claim 1, characterized in that: In terms of molar percentage, the following components are included: 76 mol% Bi2O3, 15 mol% glassy Pb3(BO3)2, 5 mol% BaO, 3 mol% Ga2O3, 0.5 mol% Cs2O and 0.5 mol% Al2O3.

3. The reverse magnetic optical rotation glass according to claim 1, characterized in that: The 1064nm absorption coefficient of the reverse magnetic rotation glass is 0.002-0.006cm -1 , 1064nm Verdet constant is 0.050~0.064min / Oe.cm, refractive index is 2.30~1.68, and glass transition temperature is 310~350℃.

4. The reverse magnetic optical rotation glass according to claim 1, characterized in that: The glassy Pb3(BO3)2 is prepared by the following steps: Step 1, grinding and mixing the formulated amount of PbO and B2O3, and drying to obtain a mixed material A; Step 2, under stirring conditions, heating the mixed material A to 750-850° C. to melt, to obtain a mixed solution B; Step 3, pouring the mixed solution B into a copper mold at room temperature, and grinding it after cooling to obtain; Wherein, the molar ratio of PbO to B2O3 in step 1 is (1.3-1.6):

1.

5. The reverse magnetic optical rotation glass according to claim 1, characterized in that: The preparation of the reverse magnetic optical rotation glass comprises the following steps: Step 1, mixing and grinding Bi2O3, glassy Pb3(BO3)2, BaO, Ga2O3, Cs2O and Al2O3 according to the formula amount to obtain a batch material; Step 2, melting, clarifying and homogenizing the batch materials to obtain reverse magnetically rotating glass liquid; Step 3, quenching, forming, heat preservation and cooling the reverse magnetic optical rotation glass liquid to obtain the product. Furthermore, in step 2, the melting temperature is 950-1000°C, the clarification temperature is 960-1100°C, the clarification time is 10-20min, the homogenization speed is 15-30r / min, and the temperature after homogenization is 750-850°C.

6. The reverse magnetic optical rotation glass according to claim 1, characterized in that: In the step 3, the quenching forming temperature is 230 to 250° C., the holding temperature is 290 to 400° C., the holding time is 240 to 720 min, and the cooling rate of the cooling treatment is -2 to -10° C. / h.

7. A magneto-optical optical fiber, characterized in that: The glass preform is made of the reverse magnetic rotation glass according to any one of claims 1 to 7.

8. A magneto-optical element, characterized in that: The magneto-optical element is made of the reverse magnetic rotation glass as described in any one of claims 1 to 7.

9. An optical instrument, characterized in that: The optical instrument is made of the reverse magnetic rotation glass as described in any one of claims 1 to 7.